The issue of training foreign medical students at the modern stage - Rusalkina, L.; Grigoriev, E.; Dekhtiar, Yu.; Ostapenko, I. (Journal of Education, Health and Sport, 2023)
Despite the war in Ukraine, medicine remained one of the most popular specialties for this year’s applicants. Ukrainian universities should work more actively on the development of innovative solutions in the field of digitization of education, the combination of mixed and modern virtual education with academic mobility. The educational space is characterized by an increase in socio-cultural complexity, the consequence of which is the complication of relations between both Ukrainian and foreign students. With this in mind, the strategic tasks of higher education in Ukraine are the formation of multicultural relationships in the student body, since almost all student groups are multicultural. The main goal of this work is to determine the features of training foreign medical students in the multicultural environment at medical higher educational institutions. The main issue today is the problem of dialogue between cultures in a multicultural environment. The importance of this question is undeniable, since the dialogue is oriented towards the future and involves deep knowledge of the spiritual structure and intellectual system of the society with which the dialogue is carried out. Multicultural education is a process of preparing individuals for social, political and economic realities in which they gain their life experience, and as a result, the individual develops his ability to perceive a multicultural environment. One of the key principles of multicultural education and upbringing is the principle of tolerance. The foreign students education process efficacy in the created multicultural environment will be facilitated by the development of skills and interpersonal communication skills. The authors concluded that foreign students’ preparation for interpersonal communication will be hindered by organizing of their creative activity by means of interactive technologies. The development of creative abilities can be ensured through the use of interactive learning tools: solving practical medical problems, solving conflict situations with patients or colleagues, role-playing, business games, applying the project method, developing associative thinking, creative independent work. The teacher should offer students of higher education a variety of individual tasks and situations, because the more actively future doctors perform them, the better their creative abilities develop. Thus, the process of multicultural education is aimed at forming socially and professionally important qualities of an individual, at creating and expanding the circle of his relations to society, to people in the surrounding world, to himself. In view of the foregoing, we conclude that the creation of a multicultural environment in a medical institution of higher education is a necessary condition for the training of foreign students in interpersonal communication. We see the prospect of further research in defining the essence of the concept of “multicultural environment of a medical institution of higher education” and clarifying the peculiarities of training foreign students - future doctors - for interpersonal communication in this environment.